HIV vertical transmission in low class populationin the South of Brazil - Stefani, Mariane (2004)
Intoduction: HIV vertical transmission is the main HIV way of infection in children, that accounts, 86,1% of cases in Brasil. Objective: the pur-pose of this paper is to establish the HIV vertical transmission index in newborn who were under care at Hospital Geral de Caxias do Sul and the HIVpositive mothers’ profile and their newborn. Methods: retrospective study of all HIV positive pregnant women and their children born betweenJanuary 2000 and December 2001 at HGCS. The data collection was carried out through mother medical records and newborn from HGCS in addi-tion to medical records from STD/AIDS Clinic. The software program used was Epi-inf. Results:the sample studied was based on 47 newborn thatcorrespond to 1,41% of the births during the period. The average age of pregnant women was 25,9 years old, 12,8% were adolescents; 74,5% haddropped out of elementary school, 34% were drug users, 80,9% had prenatal tests and 57,4% found out they were HIV positive during the prenataldiagnostic test procedure. In relation to newborn variables, 14,9% were premature babies, 4% received mother’s milk, 34% needed to go to IntensiveCare Unit, the main causes for internment were jaundice (n = 7) and congenital syphilis (n = 6). Five patients have never attended appointments at theSTD/AIDS Clinic and twelve patients underwent incomplete medical follow-up. Considering the thirty children who underwent the complete medicalfollow-up, two of them died, two were positive and twenty six were negative. Conclusion: it was not possible to evaluate the HIV vertical transmis-sion index because there was a great number of abandonment the follow-up procedure. Only thirty children underwent complete medical follow-up,therefore; we reinforce the importance of actively searching of the patients.